User friendly FE Formulation for anisotropic distortional hardening model based on non-associated flow plasticity and its application to springback prediction - Hu, Qi; Maier, Lorenz; Nishiwaki, Takeshi; Hartmann, Christoph; Volk, Wolfram; Yoon, Jeong Whan (Thin-walled structures, 2024)
•A general anisotropic distortional hardening (ADH) model is implemented based on non-associated flow in a user friendly way.•The numerical efficiency with the proposed step size for FDM integration increases by 24 %.•The maximum absolute error of flow curves between simulation and theoretical prediction is less than 0.3 %.•It is performed for DP600 both U-draw/bending test and simulation with the newly developed ADH model.•The simulation result from the distortional hardening model coincides well with the experiment. Based on non-associated flow plasticity, a newly developed anisotropic distortional hardening model developed by Hu and Yoon [15] is implemented in finite element analysis in a user-friendly manner. The derivatives of complex hardening models are calculated using the Finite Difference Method (FDM), which is much more convenient than using the analytical derivatives. To further improve the accuracy of the proposed method, the step size analysis in FDM is performed by analyzing the derivative formation. To evaluate the accuracy and computational efficiency of a proposed step size for FDM, single element simulations are performed under different loading paths. It has been found that the maximum absolute error of the flow curves between the simulation and the theoretical result is less than 0.3%. The U-bending tests for DP600 and TRIP1180 are used to verify the ability of the distortional hardening model for springback prediction. The simulation result of the strain hardening model is in good agreement with the experiment. The computational efficiency is also increased by 24% due to the improved convergence rate.